2017
DOI: 10.1038/sigtrans.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Fibromodulin reduces scar formation in adult cutaneous wounds by eliciting a fetal-like phenotype

Abstract: Blocking transforming growth factor (TGF)β1 signal transduction has been a central strategy for scar reduction; however, this approach appears to be minimally effective. Here, we show that fibromodulin (FMOD), a 59-kD small leucine-rich proteoglycan critical for normal collagen fibrillogenesis, significantly reduces scar formation while simultaneously increasing scar strength in both adult rodent models and porcine wounds, which simulate human cutaneous scar repair. Mechanistically, FMOD uncouples pro-migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 54 publications
3
58
0
1
Order By: Relevance
“…On the contrary, one-time administration of FMOD at the surgical time markedly improved the visual scar appearance of normal red Duroc pig wounds, which were identical to wounds previously assessed in adult female Yorkshire pigs [6] 8 weeks post-injury ( Fig. S3A and B).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…On the contrary, one-time administration of FMOD at the surgical time markedly improved the visual scar appearance of normal red Duroc pig wounds, which were identical to wounds previously assessed in adult female Yorkshire pigs [6] 8 weeks post-injury ( Fig. S3A and B).…”
supporting
confidence: 82%
“…In our experiment, we demonstrated that acute TAC injections did not considerably improve the gross appearance of excessive-mechanical-loading porcine wounds ( Fig. 1A and B) as assessed by an adaption of the Visual Analogue Score [6] (VAS, Fig. S2), although TAC-treated normal wounds exhibited lower VAS ( Fig.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It has been hypothesized that the pluripotent cell microenvironment plays important roles determining cell fate, as well as the maintenance and induction of pluripotency/multipotency (59). In support of this, early pioneering studies demonstrated the success- ing a fetal-like phenotype of adult dermal fibroblasts (70). FMOD is also a critical component for the maintenance of endogenous stem cell niches (71,72).…”
Section: Discussionmentioning
confidence: 99%